Churn in the older adult SNAP population. Issue 1 (24th May 2022) - Heflin, Colleen; Hodges, Leslie; Arteaga, Irma; Ojinnaka, Chinedum O.
Abstract: Using administrative records from Missouri, we investigate the characteristics of Supplemental Nutrition Assistance Program (SNAP) participants aged 60 and older who experience administrative churn. Among these adults, one in four experienced administrative churn, and one in five experienced more than one spell of churn. Risk of churn, frequency, duration of churn spells, and the value of foregone SNAP benefits varied with individual, household, and geographic characteristics, and was more common among non‐Whites, members of larger households, and those living in urban areas. Our findings suggest that a significant portion of older adults experience gaps in SNAP benefit receipt.